Psychosocial risk factors for increased emergency hospital utilization by sickle cell disease patients: a systematic review protocol. Issue 3 (March 2021) - Rech, Jean-Simon; Getten, Prunelle; Dzierzynski, Nathalie; Lionnet, François; Boëlle, Pierre-Yves; Ranque, Brigitte; Steichen, Olivier
ABSTRACT: Objective: To assess psychosocial risk factors for increased emergency hospital utilization by sickle cell patients. Introduction: Emergency hospital utilization by sickle cell disease patients is high but heterogeneous between patients and in a given patient over time. Psychosocial factors affect emergency hospital utilization and are a possible target to improve the management of sickle cell disease. Inclusion criteria: This review will include all original quantitative studies evaluating the impact of psychosocial risk factors on emergency hospital utilization by sickle cell disease patients. There will be no language restriction. Methods: PubMed, Embase, CINAHL, PubPsych, LiSSa, and Web of Science will be searched using a peer-reviewed search strategy. Study selection and extraction of data will be performed independently by two authors. Discrepancies will be solved by consensus or, if needed, by a third author. The authors will assess study quality, as well as perform a narrative synthesis of included studies, and where possible, meta-analyses with evaluation of heterogeneity and publication bias. Systematic review registration number: PROSPERO CRD42019140435.